DHA‐Enriched Phosphatidylcholine and DHA‐Enriched Phosphatidylserine Improve Age‐Related Lipid Metabolic Disorder through Different Metabolism in the Senescence‐Accelerated Mouse. Issue 6 (23rd April 2018) - Ding, Lin; Zhang, Tiantian; Che, Hongxia; Zhang, Lingyu; Xue, Changhu; Chang, Yaoguang; Wang, Yuming
Abstract : Aging is an independent risk factor for the development of atherosclerosis, which is characterized by hyperlipemia. The senescence‐accelerated mouse (SAMP8) is an animal model used in studies of aging, which is associated with a shift of fatty metabolism toward lipogenesis. This study investigates the effects of docosahexaenoic acid‐enriched phosphatidylcholine (DHA‐PC) and docosahexaenoic acid‐enriched phosphatidylserine (DHA‐PS) on age‐related lipid metabolic disorder in SAMP8 mice. Main findings and results: Both dietary DHA‐PC and DHA‐PS significantly decrease serum and hepatic lipid levels. The levels of DHA in hepatic total lipid are significantly increased in both DHA‐PC and DHA‐PS groups (2.59‐ and 2.33‐fold, respectively). Notably, supplementary DHA‐PS remarkably alters the ratio of PE to PC in liver. Mechanistically, DHA‐PC and DHA‐PS suppresses hepatic SREBP‐1c mediates lipogenesis and activates PPARα mediated fatty acid β‐oxidation in the liver. These data are the first to indicate that DHA‐PS has beneficial effects on age‐related lipid metabolism. Practical Applications : The results obtained in this work might contribute to the understanding of biological activities of DHA enriched phospholipids and further investigation on its potential application values for food supplements. This study investigates the effects of docosahexaenoic acid‐enriched phosphatidylcholine (DHA‐PC) and docosahexaenoic acid‐enriched phosphatidylserine (DHA‐PS) on age‐related lipid metabolic disorder in SAMP8 mice. The results shows that DHA‐PC and DHA‐PS improves age‐related lipometabolic disturbance by inhibiting hepatic fatty acid synthesis and enhancing hepatic fatty acid β‐oxidation, providing a reference for the development of functional ingredients rich in DHA phospholipids. Abstract : This study investigates the effects of docosahexaenoic acid‐enriched phosphatidylcholine (DHA‐PC) and docosahexaenoic acid‐enriched phosphatidylserine (DHA‐PS) on age‐related lipid metabolic disorder in SAMP8 mice. The results shows that DHA‐PC and DHA‐PS improves age‐related lipometabolic disturbance by inhibiting hepatic fatty acid synthesis and enhancing hepatic fatty acid β‐oxidation, providing a reference for the development of functional ingredients rich in DHA phospholipids.